Masjid: Lebih dari Tempat Ibadah, Jaminan Keamanan di Era Modern - Rieskha Tri Adillah EM; Uswah Khairani; Athifa Khalisha Majri; Fatimah Marzuqoh; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research explains about the mosque: apart from being a place of worship, it is also a place that guarantees security, especially in the modern era. This article aims to explore and analyze the role of mosques as institutions that function not only as places of worship, but also as a guarantee of security in the modern era. In a world that continues to change and is faced with various social and security challenges, mosques are seen as having great potential in creating stability and harmony in society. This research uses qualitative research methods. The author uses qualitative methods to analyze studies regarding the role of mosques in ensuring security in the modern era, therefore this data analysis focuses more on library research. The research results show that mosques have a significant function in maintaining security and social order through various initiatives, including centers for education and social awareness, tolerance education, overcoming radicalization and extremism, providing social and health services, involving women in mosques, and mosques as safe spaces and comfortable. Mosques, as spiritual and social centers, have a significant role in ensuring security in the modern era. By educating the public, organizing social activities, and facilitating interfaith dialogue, mosques can function as agents of peace and stability amidst global challenges. Optimizing the role of mosques in this field is very important to create a safe, harmonious and just community.